SOSIALISASI COVID-19 PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS SIMPANG TIGA KABUPATEN ACEH BESAR - Yarah, Saufa; Zuhkrina, Yuli; Maulida; Nurlaila; Sastika, Omi; Marjunita; Hastuti, Dewi (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2021)
Corona virus or severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a virus that attacks the respiratory system. The disease caused by this viral infection is called COVID-19. Corona virus can cause mild disorders of the respiratory system, severe lung infections, and even death. Coronavirus is a collection of viruses that infect the respiratory system. In most cases, this virus causes only mild respiratory infections, such as the flu. However, this virus can also cause severe respiratory infections, such as lung infections (pneumonia). According to data released by the Task Force for the Acceleration of Handling COVID-19, the number of confirmed positive cases as of June 21, 2022 was 6.069.255 people, with a death toll of 156.695. From this figure, it is known that the case fatality rate due to COVID-19 is around 2,6%. This number decreased from 3,4% in January 2022. Although the number of deaths from COVID-19 is relatively high, the recovery rate from COVID-19 is also increasing. The latest data states, the number of survivors or people who have been infected with the Corona virus and then recovered is 5.903.461 people. The method carried out is Pre Test and Post Test using a questionnaire. Based on the results of the counseling, there was an increase in the knowledge of COVID-19 respondents in pregnancy, which was in the good category by 31 (70,45%). The conclusion is that there is a significant increase in respondents' knowledge after being given counseling.